Conceptualizing Near Eastern Modernity: Religion, Politics, and Civilization. - Zemmin, Florian; Topal, Alp Eren (Welt des Islams, 2022)
The article discusses the landing of Napoleon's army near Alexandria on 1 July 1798 was considered the inception of modernity in Egypt and the wider Arab and Islamic world. This paradigm was, of course, that of modernization as Westernization, a paradigm most firmly and widely established between the 1950s and 1980s, including in research on the Near or Middle East.1 In the latter case.